Особенности УЗ-диагностики образований яичников в детском возрасте - Румянцева, З.С.; Егорова, Я.А. (Таврический медико-биологический вестник, 2010)
В статті приведені матеріали дослідження 439 дівчаток з пухлинами та пухлино подібними утвореннями яєчників. Головним методом діагностики яких була УЗ-діагностика, наведені найважливіші критерії найбільш поширених форм цієї патології. Findings of investigations of 439 patients with ovarian tumors and tumor-like formations of the ovaries presented in the article. The ultrasonic diagnostics was the main method of diagnostics of ovarian tumors, used in presented investigation. The main ultrasonic criteria of the most common form of the disease submitted as a result of investigation.